Caracterização das motivações e entraves para o produtor rural de orgânicos no Brasil - Scalco, Andréa Rossi [UNESP]; de Oliveira, Sandra Cristina [UNESP]; Cobre, Juliana (My University, 2015)
Organic agriculture was officially recognized in the 1980s, but it was in early 2000 that its development was leveraged. This study aimed to identify the factors related to the choice of organic farming by the agricultural producer, as well as recognize the main aspects considered barriers to this activity. The results showed that despite aspects related to the ideological bases being the motivators in the insertion of producer in this system, factors related to market are also taken into account. The problems noted were availability of organic seeds and lack of skilled labor. In summary, it concluded that organic production system is still progressing in Brazil, however it is necessary political and market efforts to meet this specific sector of agriculture.
Characterization of the motivations and barriers for farmers of organic products in Brazil
Keywords: Agribusiness; Organic agriculture; Organic products